Improvement Silicon Nanostructured Surface by Laser Induced Etching Process - Ibrahim, Marwa Hikmat; Rasheed, Bassam G. (Al-Nahrain Journal for Engineering Sciences, 2019)
Surface reconstruction of silicon using lasers could be utilized to produce silicon nanostructures of various features. Electrochemical and photoelectrochemical etching processes of silicon were employed to synthesize nanostructured surface. Effects of current densities 5, 10 and 20 mA/cm2 on the surface features were examined. It is found that the surface porosity and layer thickness increase with the current density. Moreover, large surface area of 410 m2/cm3 can be achieved when laser power density 0f 0.6 W/cm2 was used during the etching process. Optimum operating conditions were found to achieve better silicon nanostructured surface features. The surface roughness can be reduced to 8.3 nm using laser beam of 650 nm irradiated the silicon surface during the photoelectrochemical etching process. The surface morphology of the nanostructured silicon surface using SEM and AFM could give rich details about the surface. Silver nanoparticles of 10 – 20 nm was embedded at the nanostructured silicon surface by LIFT process to reduce the surface resistance and maintain the large surface area. This technique enables silicon nanostructures to be efficiently used in many optoelectronic applications.